Faktor-faktor yang Mempengaruhi Penilaian Mahasiswa atas Perilaku tidak Etis Auditor serta Tingkat Ketertarikan Belajar dan Berkarir di Bidang Akuntansi - Reni Yendrawati; Gaby Marcellia (Telaah Bisnis, 2016)
Abstract This research is replicated from research paper that has been done by Comunale (2006). The purpose of this research is to analyze the effect of ethic orientation, gender and knowledge on accounting profession and accounting scandal on accounting student’s assessment towards unethical auditor and its’ effect on student’s interests in accounting field and profession as auditor in accounting firm. The hypothesis testing shows that the occuring accounting scandals do not have significant effects in accounting student’s perception towards unethical auditor. However, there are factors that may affect student’s willingness and interest to study accounting and to work as auditor in accounting firm. The evidence cloncluded two accepted hypothesis: student’s knowledge on accounting profession and accounting scandal effect on declining interest to study accounting and the student’s idealism which may contribute to their falling interest on working as auditor in accounting firm.